Experimental investigation of cylindrical converging shock waves interacting with a polygonal heavy gas cylinder. (4th November 2015) - Si, Ting; Long, Tong; Zhai, Zhigang; Luo, Xisheng
Abstract : The interaction of cylindrical converging shock waves with a polygonal heavy gas cylinder is studied experimentally in a vertical annular diaphragmless shock tube. The reliability of the shock tube facility is verified in advance by capturing the cylindrical shock movements during the convergence and reflection processes using high-speed schlieren photography. Three types of air/SF6 polygonal interfaces with cross-sections of an octagon, a square and an equilateral triangle are formed by the soap film technique. A high-speed laser sheet imaging method is employed to monitor the evolution of the three polygonal interfaces subjected to the converging shock waves. In the experiments, the Mach number of the incident cylindrical shock at its first contact with each interface is maintained to be 1.35 for all three cases. The results show that the evolution of the polygonal interfaces is heavily dependent on the initial conditions, such as the interface shapes and the shock features. A theoretical model for circulation initially deposited along the air/SF6 polygonal interface is developed based on the theory of Samtaney & Zabusky ( J. Fluid Mech., vol. 269, 1994, pp. 45–78). The circulation depositions along the initial interface result in the differences in flow features among the three polygonal interfaces, including the interface velocities and the perturbation growth rates. In comparison with planar shock cases, there are distinct phenomena caused by the convergence effects, including the variation of shock strength during imploding and exploding (geometric convergence), consecutive reshocks on the interface (compressibility), and special behaviours of the movement of the interface structures (phase inversion).